Fiandeira de versos: o imaginário do tecer poético de Hilda Hilst - Morais, Aline Pires de (2010)
The lyric production of Hilda Hilst (1930 - 2004) is marked by the use of symbolic images that amplify endlessly the possibilities of reading her poems. In her knowledge about the world, the poet discovers the cosmos that surround the time which presents her views recast by the poetic reverie. The symbols used by Hilst are expressions of a soul that made the poetry her life during the search of the color, of the link, the wire, the motion of the shuttle, the precision, the texture of the line, finally, of the exact moment of manipulation the wired-word‟. According to this, the eyes of search return to the study of images made by the author, mainly, from the universe weaver. During the investigation of the poetic figurations imagery in the Hilst‟s text, we will consider the imagination like a creative dynamism in the corpus of selected poems from the books: Júbilo, memória, noviciado da paixão and Exercícios. These productions of Hilst legacy show images of the inspired poet and the weaver poet in verses guidelines that combine the strength of the intellect and the need for expression, linked to the poet desire to make the experience of living the raw material of her poems. Thus, the analytical work of the critical myths in the Hilst‟s poems plans to mark the divine nature of human existence, because the poet is spinner, and wired-words‟ are handled under the gift of art, sometimes under the prophetic gift, or under the simultaneous combination of both, the inspiration and work. The Hilda Hilst‟s poetry, connection between prophecy and incantation, it is a mediator between the sphere of the profane and the sacred, capable of making stocks and destinations by the incantation of her corner that leads and snatch. Thus, the voice of Hilst‟s poetry, symbolic representation of the alliance of the words in the fabric of poetic images, protest as an oracle of life that, sanction the reality, can lead to the rapture of the tangent experience to the sacred and, getting to the unflagging unity between poetry and music, can promote the man catharsis in front of his simple reality.